Lack of cardiac remodelling in elite endurance athletes: an unexpected and not so rare finding - Di Gioia, G.; Crispino, S. P.; Maestrini, V.; Monosilio, S.; Ortolina, D.; Segreti, A.; Squeo, M. R.; Lemme, E.; Nenna, A.; Pelliccia, A. (European Journal of Applied Physiology, 2024)
Purpose Endurance elite athletes are expected to present a cardiac remodelling, characterized by eccentric hypertrophy (EH), may be associated with higher sportive performances. However, not all can present a cardiac remodelling. The study aimed to identify endurance athletes without cardiac remodelling characterizing their physiologic and clinical features.